Conversion of NOx1− (x = 2, 3) to NO using an oxygen-deficient polyoxovanadate–alkoxide cluster. Issue 4 (12th December 2019) - Petel, Brittney E.; Matson, Ellen M.
Abstract : We report the activation of nitrogen-containing oxyanions using an oxygen-deficient polyoxovanadate–alkoxide cluster. Abstract : We report the activation of nitrogen-containing oxyanions using an oxygen-deficient polyoxovanadate–alkoxide cluster. Reduction of NO2 1− and NO3 1− results in near-quantitative oxygen atom transfer to the coordinatively unsaturated V III ion, and selective formation of NO. These results provide insight into possible mechanisms of oxyanion reduction by polyoxometalates.